О применении интерфейса PCI-Express для построения компьютерных систем с использованием ПЛИС - Яковлев, Ю.С. (Управляющие системы и машины, 2016)
Показано преимущество интерфейса типа PCI-Express перед другими разновидностями интерфейсов и приведены его основные характеристики. Рассмотрены структурные схемы организации PCI-Express для отдельных систем, а также модули PCIExpress, выполненные на соответствующих платах, которые имеют различные наборы линий передачи данных типа «точка–точка». Показано перевагу інтерфейсу типу PCІ-Express перед іншими різновидами інтерфейсів та наведено його основні характеристики. Розглянуто структурні схеми організації PCІ-Express для окремих систем, а також модулі PCІ-Express, які виконано на відповідних платах і мають різні набори ліній передачі даних типу «крапка–крапка». The features of data transfer based on PCI Express and appropriate resources of support in the various computer systems using for these purposes the PLIS are defined. The features of physical implementation PCI Express in the form of units with their parametres, lines supporting various quantity for a simultaneous (parallel) information transfer of type “point-point” to rise the productivity of system are researched. The parameters and advantages of the PCI Express comparing with the other types of interfaces have lighted a wide range of questions: the alternatives of block schemes of the computer systems, using this interface, resources of the interface support, alternatives of units (cards) with implementation PCI Express. The possible alternative of the block diagram of such type for the technological system with usage PCI Express and assemblage of the sensors of the data which preparative treatment is fulfilled on assemblage connected by means of the cables PLIS through appropriate adapters is offered. As to an urgency of the given operation it is possible to mark the following. First, PCI Express became the data transfer standard between CPU, system memory and apparatus accelerators (GPU) in tasks High Performance Computing (HPC). Secondly, PCI Express demands can be adapted for devices of any type, providing thus an information transfer high speed - from a mobile phone to a server of level of firm. Thirdly, parameters PCI-Express essentially exceed now parameters of the majority of interfaces of other types. And, the fourth, such interface can be used for other types of the carrying agents built by other physical principles. The informationcan be useful by developers, who are engaged in designing of systems with PCI Express use, sets data gathering means and set PLIS, the data focused on preliminary processing.